Development of a new ergonomic risks management algorithm on the example of drivers - Tsopa, Vitaliy; Cheberiachko, Serhii; Cheberiachko, Yurii; Deryugin, Oleg; Chencheva, Olga; Rieznik, Dmytro; Klimov, Eduard; Lashko, Yevhenii; Pashko, Dmytro; Biliaieva, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study: the process of determining and managing ergonomic risks at workplaces when performing professional activities on the example of truck drivers. The problem lies in uncertainty when making decisions in occupational safety and health management systems. The hypothesis of the study was the possibility of assessing ergonomic risks in the occupational safety management systems of organizations based on the identification of regularities between the load index, typical working postures when performing operations and the intensity of joint movements. An ergonomic risk assessment algorithm was developed, taking into account the load index, which includes a sequence of eleven steps, which can be conditionally divided into three groups. The first is determination of the intensity of joint movement. The second is the determination of the impact of activity and the duration of the production task. The third is determining the impact of environmental factors. An assessment of the ergonomic risk of drivers was carried out for three types of production work: driving a vehicle, replacing a damaged wheel, and repairing a car. At the same time, the ergonomic risk assessment algorithm takes into account the worker’s individual state of health and environmental factors, as well as experience and work experience. It has been established that there is a high level of ergonomic risk during car maintenance due to the highest total load index, which is 30 % higher compared to other types of work of vehicle drivers. The practical application consists in the development of a universal check list of drivers based on an algorithm to determine the ergonomic risk of workers at workplaces, which consists of 11 steps